Reduksi Cacat Retak pada Proses HPCM melalui Integrasi Six Sigma, FMEA, dan DOE - Abby Yazid Bustommy; Rangga Wahyu Fattahillah; Lifia Citra Ramadhanti (UNISTEK, 2026)
The sanitary ware industry requires stable production processes because defects in ceramic products are critical and difficult to repair. PT RII experienced quality problems in the BN 150 G squat toilet product manufactured using the High Pressure Casting Machine (HPCM) process. Initial data indicated a defect rate of 8.55%, exceeding the company tolerance limit of 4%. This study aims to measure process capability, identify the main causes of crack defects, determine failure risk priorities, and establish the optimum air pressure parameter to reduce defects. The study employed the Six Sigma method with the Define, Measure, Analyze, Improve, and Control (DMAIC) approach integrated with Failure Mode and Effect Analysis (FMEA) and Design of Experiment (DOE). The results showed that the initial process condition had a Defects Per Million Opportunities (DPMO) value of 21,400 with a sigma level of 3.52. FMEA analysis identified unstable air pressure as the most critical cause of defects, with the highest Risk Priority Number (RPN) of 576. DOE results indicated that an air pressure of 3 bar produced the lowest defect proportion and had a significant effect on product defect status (p-value = 0.041). After improvement, the DPMO decreased to 17,000 and the sigma level increased to 3.62. These findings demonstrate that the integration of Six Sigma, FMEA, and DOE is effective in reducing crack defects and improving HPCM process capability in the sanitary ware industry.